2021
DOI: 10.1002/bse.2716
|View full text |Cite
|
Sign up to set email alerts
|

Circular business model evolution: Stakeholder matters for a self‐sufficient ecosystem

Abstract: Food waste is a key issue in the circular economy. A circular ecosystem results from the contributions of various stakeholders; however, the claims and value propositions of these stakeholders can differ, hampering long-term sustainability of the ecosystem. This study analyses the case of RiCibo, a circular ecosystem based in Genoa, Italy. RiCibo collects surplus food and redistributes it to the needy in the local community. The study examines the conditions that facilitated RiCibo's evolution from a simple pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 90 publications
1
42
0
1
Order By: Relevance
“…A number of factors drove evolution towards a thrivable entrepreneurial ecosystem. Similar to previous studies (Moggi & Dameri, 2021;Parida & Wincent, 2019), the results showed that the sharing of knowledge and tools with a common goal was possible thanks to the profitable returns from the cooperation among entrepreneurs. Collected public and European funds and the savings in economic scale made possible by the recovery and reuse of discharged resources (such as land) enabled an increase in thrivability of the system and attracted young entrepreneurs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A number of factors drove evolution towards a thrivable entrepreneurial ecosystem. Similar to previous studies (Moggi & Dameri, 2021;Parida & Wincent, 2019), the results showed that the sharing of knowledge and tools with a common goal was possible thanks to the profitable returns from the cooperation among entrepreneurs. Collected public and European funds and the savings in economic scale made possible by the recovery and reuse of discharged resources (such as land) enabled an increase in thrivability of the system and attracted young entrepreneurs.…”
Section: Discussionsupporting
confidence: 86%
“…Researchers suggest that the success of ventures depends on appropriate public and private support systems (Cavallo et al, 2019;Nylund & Cohen, 2017) as well as several institutional conditions including regulatory policies, innovation climates and social norms (Morozova et al, 2019;Sunny & Shu, 2019). In this context, entrepreneurship is usually orchestrated by a focal organisation and the ecosystem is characterised by transparency in the actors' actions (Moggi & Dameri, 2021;Parida & Wincent, 2019;Stam, 2018).…”
Section: Sustainable Entrepreneurship and Sustainable Entrepreneurial Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these new approaches, an SI feature my also involve, for example, a specialization in SF supply channels, such as those realized by Recup and Ecomori in Italy, to recover SF from city markets, or by Equoevento, which recovers leftovers from catering events [67][68][69]; it may also concern the management system for a recovery network, such as the one provided by Refood in Portugal, which operates with a particular focus on communitybuilding and citizen participation at a local level [70], or by Avanzi Popolo 2.0 in Italy, which works to create new connections between heterogeneous stakeholders [19]. Food recovery governance can also take the form of public-private networks, as occurs in Genoa (Italy) with Ricibo, a social platform involving non-profit organizations, the local Municipality and traditional businesses cooperating in SF recovery as a circular business model [71].…”
Section: Human Reusementioning
confidence: 99%